Enhancing Students’ Speaking Through the Process of Performing Drama - Dian Anggraini (Register Journal, 2014)
An action research has always been interesting thing for teacher because the root of it is taken from their own problems. This study is a self reflection of a problem that is faced by the researcher. It focuses on a certain activity in a certain class and at a certain period of time. Questionnaires, interview sheet, observation sheet, students’ worksheets, and teacher’s lesson plans serve as data resources. The result shows a significant increase in the students score. However, there is variation on the general result. Keywords:collaborative learning; drama ; motivation